The Influence of E-Banking Service Quality, Marketing Communication, and Corporate Image on Customer Satisfaction and Its Impact on Customer Loyalty (Survey on Indonesian Sharia Banks in East Priangan, West Java) - Nila Nurochani; Eddy Jusuf; Undang Juju (Politeknik APP Jakarta, 2023)
The success of the performance of Bank Syariah Indonesia in East Priangan, West Java (BSI), one of which will depend on the quality of marketing management carried out by BSI, which in turn will be able to increase customer satisfaction and customer loyalty. This study aims to determine and examine the effect of E-Banking Service Quality, Marketing Communication and Corporate Image on Customer Satisfaction and Their Impact on BSI Customer Loyalty in Priangan Timur, West Java. This study uses quantitative methods with descriptive analysis and verification analysis. In this study, the samples were customers with a total sample of 400 customers. The method of analysis in this study uses the Structural Equation Model (SEM) analysis. The results of the study conclude that there is a significant effect of the quality of E-Banking Services.